2015
DOI: 10.1002/2014jb011782
|View full text |Cite
|
Sign up to set email alerts
|

The fate of fluid inclusions during high‐temperature experimental deformation of olivine aggregates

Abstract: Torsion experiments on initially wet and dry olivine aggregates at equivalent deformation conditions investigated the fate of fluid inclusions (FIs) during high-temperature deformation. Wet samples were produced by adding water to San Carlos olivine powders before hot pressing; those hot pressed without water are considered dry. After hot pressing, wet and dry aggregates have comparable grain sizes, but wet aggregates have more abundant primary FIs. Talc jackets were fitted around some wet and dry samples prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…An alternative possibility for the relative enrichments in Ba without enrichments in LREE would be a component derived from (altered) oceanic crust during a past episode of subduction (Figure 9b). Melts of altered oceanic crust have too anomalously high Zr/Hf and Hf/Sm to be a likely candidate [Carter et al, 2015], whereas hydrous fluids derived from altered oceanic crust may account for some of the intraplate-like enrichment [Green and John, 2003]. We suggest below that the contribution from the intraplate-like component is greatest in melts that are mostly derived from a deep source, leading us to favor contributions from an intraplate mantle over contributions from a subducted slab.…”
Section: The Intraplate-like Mantle Componentmentioning
confidence: 81%
See 1 more Smart Citation
“…An alternative possibility for the relative enrichments in Ba without enrichments in LREE would be a component derived from (altered) oceanic crust during a past episode of subduction (Figure 9b). Melts of altered oceanic crust have too anomalously high Zr/Hf and Hf/Sm to be a likely candidate [Carter et al, 2015], whereas hydrous fluids derived from altered oceanic crust may account for some of the intraplate-like enrichment [Green and John, 2003]. We suggest below that the contribution from the intraplate-like component is greatest in melts that are mostly derived from a deep source, leading us to favor contributions from an intraplate mantle over contributions from a subducted slab.…”
Section: The Intraplate-like Mantle Componentmentioning
confidence: 81%
“…Of these, the similarity between the Pb isotope signatures inferred for the subductionmodified mantle domain and eastern Mediterranean sediments, as well as the trend of e Hf and e Nd (Figure 4), suggest that Mediterranean Neotethyan sediments and/or derivative fluids are likely Geochemistry, Geophysics, Geosystems 10.1002/2016GC006772 responsible for the distinct chemical and isotopic characteristics of the subduction-related contribution to the Hasan Monogenetic Cluster basalts. Melts or fluids derived from oceanic crust [Elliott, 2003;Carter et al, 2015], in contrast, cannot account for the unradiogenic Nd and Hf isotopes of the subductionmodified mantle, nor its relatively high La/Sm and Th/Nb (Figures 7 and 9). Because certain trace element characteristics of the basalts, most notably La/Sm, overlap those of sediments, the agent for subductionrelated contamination of the mantle may be sediment melts, rather than sediments themselves.…”
Section: The Subduction-modified Mantle Domainmentioning
confidence: 99%
“…The high-conductivity anomalies have been shown to occur in relatively cold subduction zones, which might be caused by the presence of aqueous fluids (Pommier and Evans, 2017). Previous studies of fluid inclusions in deep Earth rocks and hightemperature and high-pressure experiments have demonstrated that aqueous fluids with some form of volatile and salt species are abundant in subduction zones (Carter et al, 2015;Huang et al, 2019;Lacovino et al, 2020). NaCl-bearing aqueous fluids have been proposed to be the most significant saline fluid in subduction environments because Na + and Cl − are the most dominant ions in most saline fluid inclusions (Morikawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%